32.3k views
1 vote
Pls help I don’t understand

Pls help I don’t understand-example-1

2 Answers

4 votes
distributive property!

3 (2 + x) - 2 (5 -2x)
turns into

6 + 3x -10 + 4x

now combine terms

final answer: -4 + 7x
User Tesseract
by
6.0k points
4 votes

3(2+n)-2(5-2n)

Mutiply the first bracket by 3

(3)(2)= 6

(3)(n)= 3n

Mutiply the second bracket by -2

(-2)(5)= -10

(-2)(-2n)= 4n

6+3n-10+4n

6-10+3n+4n ( combine like terms )

-4+7n or 7n-4

Answers: -4+7n or 7n-4

User Franc Weser
by
6.6k points